A Comparative Analysis on the Concept of Culture and Period of Vedic In Ancient India: Unraveling the Cultural Significance of the Vedic Period in Ancient India (Journal of Advances and Scholarly Researches in Allied Education, 2013)
The Vedic Period is one of major milestones in thehistory of India.It is estimated that the Vedic Period in India lasted from 1500 - 600 B.C.This period brought about a multitude of changes in the lifestyle of people.The Vedic age is broadly classified into two categories: Early Vedic Age andLater Vedic age. There was development in agricultural practices, worshippingpatterns, philosophical outlooks, etc. A number of dynasties and new religionscame into being during this period that left a huge impact on people. Read onthe history of the Vedic Age. The migration of the Aryans to the Indian sub-continentis what triggered off the Vedic Age. As the name suggests, this period got itsname from the four major Vedas or the sacred scriptures that were createdduring that time. The four sacred Vedas are Rig Veda, Sama Veda, Yajur Veda andAtharva Veda. These scriptures provide essential knowledge of the lifestyleduring the Vedic Age. The Vedas are the foundation of the Hindu religion. Apartfrom the Vedas, we have two great epics, Ramayana and Mahabharata writtenduring this age. These two epics tell a lot about the culture, society,religious beliefs, etc. of people during that time. The religion of Vedic India was sacrificing based, takingas its example the primordial sacrifice of the god Purusa. Because of theimportance of sacrifice, the gods Soma and Agni were among the most importantin the Vedic pantheon. Agni was the god of the sacrificial fire, and Soma thegod of the sacred drink and the moon. It was against this backdrop that further Indiancivilization was to develop. Both the golden age of Asoka's rule, Buddhism, andmodern Indian culture are all rooted in the Vedic age. It was at this time thatthe essential 'great ideas' were formed, though it would take many morecenturies for them to come to their full glory.